Ozonation of polyoxymethylene effluent in a rotating packed bed. Issue 7 (21st March 2019) - Wang, Dan; Wang, Wei; Liu, Taoran; Shan, Mingjun; Li, Guangjun; Arowo, Moses; Shao, Lei
ABSTRACT: This work aimed to investigate the effectiveness of ozone in degradation of polyoxymethylene (POM) effluent in a rotating packed bed (RPB) (O3 -RPB system). The degradation efficiency was evaluated in terms of chemical oxygen demand (COD), 5-day biological oxygen demand (BOD5 ) and BOD5 /COD under various operating conditions. Pilot experiments comprising the O3 -RPB unit coupled with a biological contact oxidation unit were also carried out. The COD removal rates in the pilot process increased markedly to about 70–85% compared to about 40% in the original treatment process, which is the tertiary aerobic treatment in the plant, confirming that the O3 -RPB system is very efficient in improving the biodegradability of the POM effluent.